Can the Use of Video Learning Increase Student’s Interest in Traditional Music? - Mustofa, Septhea Pradina; Wihidayat, Endar S.; Hatta, Puspanda (Universitas Sebelas Maret, 2018)
Nowadays, video increasing its popularity and becomes alternatives media used for education. It's popularity in line with the extensive access to online video such as Youtube, Netflix, etc. This research aims to compare learning outcomes between textbook and video specifically at students interest to Indonesian traditional music, named Gamelan. Quasi-experimental Design method used to compare those two learning media. Three phases of activities are conducted in this study: 1) preparing the video learning media, 2) testing learning media on experimental class and control class 3) taking questionnaires and analyze the result. The number of samples was 182 students, chosen from local students at a vocational high school at Boyolali, a city in Central Java Province, Indonesia. The results showed both of learning media increase the student interest. But the video increase student interest more significant. Using the textbook, we got 77,58% meaning